Literature classification on dispatching of container terminal vehicles - Anne Kathrina Schwientek; Ann-Kathrin Lange; Carlos Jahn (Digitalization in Maritime and Sustainable Logistics: City Logistics, Port Logistics and Sustainable Supply Chain Management in the Digital Age. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 24, 2017)
Horizontal transport on container terminals represents the interface between quay and yard. Efficient transport operations are essential to improve performance and productivity. Thereby, one main decision problem is dispatching the vehicles. Despite the large amount of literature in this field, there is no classification or survey of the respective literature. Based on an extensive survey of dispatching literature published between 2000 and 2016, a classification scheme is developed and applied to 81 scientific publications. The classification serves as a framework to propose a definition of dispatching - distinguishing it from scheduling - and to identify trends and potential for future research. The understanding of 'dispatching' differs significantly from assigning tasks to vehicles to developing exact schedules for the vehicles. Another substantial difference is whether the dispatching problem is considered separately from other terminal operations or integrated. Influencing factors on the ranking of dispatching methods are hardly investigated. The classification scheme provides for the first time a comprehensive background for classification of dispatching literature. It comprises a large list of criteria in three categories: problem characteristics, solution method and performance evaluation. Thereby, this paper provides a basis to derive further research activities.
urn:nbn:de:gbv:830-88217825; 10419/209193; https://econpapers.repec.org/RePEc:zbw:hiclpr:24
Keywords: 650; Container terminal; Horizontal transport; Literature survey and classification; Dispatching